Evaluating progression of liver disease from repeat liver biopsies in children with chronic hepatitis C: A retrospective study. Issue 5 (30th September 2013) - Mohan, Parvathi; Barton, Bruce A.; Narkewicz, Michael R.; Molleston, Jean P.; Gonzalez‐Peralta, Regino P.; Rosenthal, Philip; Murray, Karen F.; Haber, Barbara; Schwarz, Kathleen B.; Goodman, Zachary D.
Abstract : Clinical and histologic progression of liver disease in untreated children with chronic hepatitis C virus (HCV) infection is poorly documented. The aim of this retrospective study was to characterize changes in liver histology over time in a cohort of HCV‐infected children who had more than one liver biopsy separated by over 1 year. Forty‐four untreated children without concurrent liver diseases, who had repeat liver biopsies at eight U.S.‐based medical centers, were included. Biopsies were scored by a single pathologist for inflammation, fibrosis, and steatosis and were correlated with demographic data including age at biopsy, time from infection to biopsies, and laboratory values such as serum alanine aminotransferase (ALT). Mode of transmission was vertical in 25 (57%) and from transfusions in 17 children (39%). Genotype 1 was present in 30/35 (84%) children. The mean age at first and final biopsy was 8.6 and 14.5 years, respectively, and the mean interval between biopsies was 5.8 ± 3.5 years. Duration of infection to biopsy was 7.7 and 13.5 years, respectively. Laboratory values did not change significantly between the biopsies. Inflammation was minimal in about 50% at both timepoints. Fibrosis was absent in 16% in both biopsies, limited to portal/periportal in 73% in the first biopsy, and 64% in the final biopsy. Between the two biopsies, the proportion of patients with bridging fibrosis/cirrhosis increased from 11% to 20% ( P = 0.005). Conclusion : Although in aggregate this cohort did not show significant histologic progression of liver disease over 5 years, 29.5% (n = 13) of children showed an increase in severity of fibrosis. These findings may have long‐term implications for the timing of follow‐up biopsies and treatment decisions. (Hepatology 2013;58:1580–1586)